MANAHIJ AL-MUHADDISUN ULAMA SUFI - Idris Siregar (SHAHIH (Jurnal Ilmu Kewahyuan), 2021)
This paper is presented to provide an overview of the methods of the Sufi Ulama muhaddisun in an effort to assess the position and role of hadith for Muslims as an Islamic scientific tradition. The methodology used in this paper is library research. Sufi experts acknowledge the method of transmitting hadith that has developed among hadith experts. Among hadith scholars, hadith transmission uses certain standard methods as seen in the hadith sanads. The transmission came from the Prophet and then passed on to his companions, then to the tabi'in, and so on until the mukharrij hadith (scholars who recorded hadiths). This is different from the hadith transmission system among tasawwuf experts who use the liqa' al-Nabi and kashf methods, which state that a Sufi, with a high level of spirituality, can meet the Messenger of Allah and narrate hadiths directly from him either through dreams or while awake. (not sleeping). According to them, the hadith obtained in this way is authentic even though there is no sanad in it.